2016
DOI: 10.3823/2011
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic Performance of Shoulder External and Internal Rotators in Adolescent Male Volleyball Athletes

Abstract: Background: Volleyball is a sport characterized by short, intensive and explosive actions. In the performance of these repetitive movements, the shoulder joint receives the largest load. Therefore, a detailed assessment of biomechanics and muscle performance is fundamental in the evaluation, treatment and in prevention of shoulder injuries in volleyball athletes. Methods and Findings:Information from a database concerning the isokinetic evaluation of the shoulder's external and internal rotator muscles at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
1
0
2
Order By: Relevance
“…There were not significant differences in ER/IR ratio between both groups neither in both velocities, but the ER/IR ratio values were a little more than normal ratio values (ER/IR norm value of 65%-75%) 68,[70][71][72] for both male and female players. This results are in line with the findings of Franceschini et al, 60 in which the protocols and movements of the study were the same as our study but in Brazilian Volleyball players' population. A study found a relationship between an abnormal ER/IR ratio and the incidence of shoulder injuries among athletes of overhead sports.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…There were not significant differences in ER/IR ratio between both groups neither in both velocities, but the ER/IR ratio values were a little more than normal ratio values (ER/IR norm value of 65%-75%) 68,[70][71][72] for both male and female players. This results are in line with the findings of Franceschini et al, 60 in which the protocols and movements of the study were the same as our study but in Brazilian Volleyball players' population. A study found a relationship between an abnormal ER/IR ratio and the incidence of shoulder injuries among athletes of overhead sports.…”
Section: Discussionsupporting
confidence: 94%
“…These results illustrated muscle strength asymmetry in the glenohumeral of SV players, with the dominant upper extremity tending to produce greater values for PT compared to the nondominant side. These findings were in agreement with some studies with similar protocols of this study, but among elite conventional volleyball players from different countries which include: Franceschini et al 60 and Maledonça et al 61 (Brazilian players), Hadzic et al 62 (Slovenian players), Markou and Vagenas 63 (Greek players), Michael et al 64 (German players), Van Cingel et al 65 (Dutch players), and Wang et al 66 (English players).…”
Section: Discussionsupporting
confidence: 92%
“…In the study of sprint canoe athletes, in which the demands during the stroke are unilateral, Humphries et al (2000) did not show significant differences between the members in the analysis of ER and IR; however, they demonstrated isokinetic strength imbalance between the DL and NDL for flexors and extensors of the shoulder joint. Isokinetic studies with adolescent athletes of other sports with unilateral requirements of upper limbs such as volleyball (Franceschini et al, 2016), handball (Dos Santos Andrade et al, 2013), tennis (Ellenbecker et al, 2003;Saccol et al, 2010), and baseball (Noffal, 2003;Hurd et al, 2011), also showed differences between the limbs, with the MD presenting higher values of PT of the ER and/or IR.…”
Section: Discussionmentioning
confidence: 99%
“…Os resultados do presente estudo não demonstraram diferenças estatisticamente significativas na velocidade angular de 180º/s, entretanto a 60º/s o MD apresentou valores médios significativamente superiores ao do MND, tanto para a musculatura RE como da RI na análise do PT. Estudos isocinéticos com atletas de modalidades esportivas assimétricas, como voleibol [17,[19][20][21][22][23], handebol [24,25], tênis [26][27][28], basebol [29,30] e polo aquático [31] também demonstraram que o MD apresenta valores maiores de PT dos RE e/ou RI. A utilização preferencial de um dos membros durante os principais movimentos de uma determinada prática esportiva faz com que haja um aumento da força muscular desse membro.…”
Section: /7unclassified